Dampak Ekspansi fiskal terhadap inflasi: Studi empiris dengan pendekatan error correction model - Jaka Sriyana (Economic Journal of Emerging Markets, 2001)
In fact, for the first of long-term development Indonesia has achieved successfully the high rate of economic growth. But, in this period a high rate of inflation occured. Since 1960 government has applied a deficit fiscal, in which total expenditure is over domestic income.